Y=x^(3)-4x^(2)-3x+5 y=x(x2-4x-3+5) x2-4x+2=0 D=(-4)-2*(-1)*2=16+4=20 x1=4-2√5/2=2(2-√5)/2=2-√5 x2=4+2√5/2=2(2+√5)/2=2+√5 y1=2-√5((2-√5)2-4*2-√5-3+5) y1=2-√5(4-5-4*2-√5-3+5) y1=2-4√5-5√5-4√5*2√5-√25-3√5+5√5)2-√5 y1=-3-15√15 (2-√5;-3-15√15)V(2+√5;y2) решение не полное нужно ещё найти y2 просто подставить в первой уравнение.
y=x(x2-4x-3+5)
x2-4x+2=0
D=(-4)-2*(-1)*2=16+4=20
x1=4-2√5/2=2(2-√5)/2=2-√5
x2=4+2√5/2=2(2+√5)/2=2+√5
y1=2-√5((2-√5)2-4*2-√5-3+5)
y1=2-√5(4-5-4*2-√5-3+5)
y1=2-4√5-5√5-4√5*2√5-√25-3√5+5√5)2-√5
y1=-3-15√15
(2-√5;-3-15√15)V(2+√5;y2)
решение не полное нужно ещё найти y2 просто подставить в первой уравнение.